Legal Protection of Patient Personal Data in Telemedicine Practice: Aligning the Health Law and the Personal Data Protection Law - Agus Arya Mahottama; I Gde Sastra Winata (Jurnal Indonesia Sosial Sains, 2026)
Digital transformation in Indonesia's health sector has accelerated the adoption of telemedicine services as an alternative to remote medical services. Although these services provide efficiency and expand healthcare access for the broader community, the practice of telemedicine raises serious juridical challenges, particularly regarding the protection of highly sensitive patient personal data. This research aims to analyze the juridical aspects of patient personal data protection in telemedicine services and examine the urgency of synchronizing the Health Law and the Personal Data Protection Law (PDP Law). Using a normative juridical legal research method with statutory and conceptual approaches, the findings indicate that a legal framework is available in Indonesia through Law No. 17 of 2023, Law No. 27 of 2022 (PDP Law), and Minister of Health Regulation No. 20 of 2019. However, there are regulatory inconsistencies, a void of technical norms, as well as weak infrastructure and human resource awareness that make patient data vulnerable to leaks. The synchronization of regulations and the adoption of international standards such as GDPR (General Data Protection Regulation) and HIPAA (Health Insurance Portability and Accountability Act) are urgently needed to create legal certainty, guarantee medical data confidentiality, and provide maximum protection for patients and healthcare workers.